Non-destructive evaluation of an internal adaptation of resin composite restoration with swept-source optical coherence tomography and micro-CT. Issue 1 (January 2016) - Han, Seung-Hoon; Sadr, Alireza; Tagami, Junji; Park, Sung-Ho
Highlights: Micro-CT and SS-OCT may be useful non-destructive methods for evaluating internal adaptation. The microleakge measured by micro-CT was lower than that of SS-OCT, however the two measurements were relatively high-correlated. When adhesion depends mostly on the dentin surface, a two-step self-etch adhesive system should be considered for long-term longevity. Abstract: Swept-source optical coherence tomography (SS-OCT) and micro-CT can be useful non-destructive methods for evaluating internal adaptation. There is no comparative study evaluating the two methods in the assessment of internal adaptation in composite restoration. The purpose of this study was to compare internal adaptation measurements of SS-OCT and micro-CT. Two cylindrical cavities were created on the labial surface of twelve bovine incisors. The 24 cavities were randomly assigned to four groups of dentin adhesives: (1) three-step etch-and-rinse adhesive, (2) two-step etch-and-rinse adhesive, (3) two-step self-etch adhesive, and (4) one-step self-etch adhesive. After application, the cavities were filled with resin composite. All restorations underwent a thermocycling challenge, and then, eight SS-OCT images were taken using a Santec OCT-2000™ (Santec Co., Komaki, Japan). The internal adaptation was also evaluated using micro-CT (Skyscan, Aartselaar, Belgium). The image analysis was used to calculate the percentage of defective spot (%DS) and compare the results. The groups were compared using one-way ANOVA with Duncan analysis at the 95% significance level. The SS-OCT and micro-CT measurements were compared with a paired t -test, and the relationship was analyzed using a Pearson correlation test at the 95% significance level. The %DS results showed that Group 3 ≤ Group 4 < Group 1 ≤ Group 2 on both SS-OCT and micro-CT images. The %DSs on micro-CT were lower than SS-OCT ( p < 0.05) and the Pearson correlation coefficient between SS-OCT and micro-CT was r = 0.787 ( p < 0.05).